Análisis de la competitividad de Colombia en el sector turístico en el periodo 2011-2018 (2019)
The diversity of Colombia makes this country with great tourism potential, being one of the sectors that generates the most foreign currency in the country, only surpassed by oil exports and its derivatives. The present work has been carried out with the objective of analyzing the competitiveness of Colombia in the tourism sector, through a collation of information a bibliographic search was carried out with the purpose of identifying the different models of models to quantify the tourist competitiveness of a country, to subsequently select the model most appropriate to our research, and to analyze the variables that determine the tourism competitiveness of a country, in addition, to relate them to the volumes of tourism corresponding to the 2011-2018 period.